The impact of brand activism on consumer behavior: a theoretical and empirical analysis in the context of sport brands - Rosa, Anderson Filipe (2025)
Brand activism occurs when companies take public stances on sensitive sociopolitical issues such as racism, gender justice or sustainability, aligning their institutional discourse with ethical values and social demands. This practice has become increasingly common in contemporary marketing, driven by consumer expectations and the symbolic role that brands play in public discourse. In this context, this dissertation investigates how different forms and sources of brand activism influence consumer behavior, with an emphasis on the sports sector, where various types of brands such as athletes, clubs, sponsors and governing bodies share symbolic space and interact continuously with the public. The dissertation is structured around three interrelated academic articles. The first presents a systematic literature review, organizing empirical evidence through the lens of the Theory of Planned Behavior and identifying key psychological variables involved in consumer responses. The second article applies an experiment to analyze how different brand activism strategies authentic, inauthentic, silent and absent influence consumer attitudes and brand trust, considering perceived authenticity and value alignment. The third article, based on a quasi- experiment, investigates how activism from different types of brands in the sports ecosystem specifically athletes, clubs, sponsors and governing bodies influences consumer perceptions, particularly regarding brand image and trust. Together, the three studies offer theoretical and empirical contributions to understanding how consumers respond to brand activism in different contexts, articulating both individual and contextual variables. The thesis also provides practical implications for brands aiming to position themselves strategically, coherently and in alignment with consumer expectations.